Polymeric biomaterials for wound healing - Oliveira, Cristiana; Sousa, Diana; Teixeira, José A.; Ferreira-Santos, Pedro; Botelho, Claudia M. (Frontiers in Bioengineering and Biotechnology, 2023)
Skin indicates a person's state of health and it is so important that influences a person emotional and psychological behaviour. In this context, effective wound care is one of major concern as several conventional wound healing materials have been unsuccessful to provide proper healing, leading, many times, to the formation of scars. Hence, the development of innovative biomaterials for wound healing is essential. Natural and synthetic polymers are used extensively for wound dressings and scaffolds production. Both natural and synthetic polymers have beneficial properties and limitations, so they are often used in combination to overcome the limitations of each. The use of different polymers in the production of biomaterials has proven to be a promising alternative for the treatment of wounds, as their capacity to accelerate the healing process has been demonstrated in many studies. Thus, this work focuses on describing several solutions used for the management of skin wounds, such as polymeric biomaterials for skin substitutes, currently commercially available. New directions, strategies and innovative technologies for the design of polymeric biomaterials are also addressed, providing solutions for deep burns, personalized care and faster healing.